Impact of land use/land cover dynamics on himalayan wetland ecosystem - Bhat¹ and Ashaq Hussain Sheikh³, Akhtar Alam¹*, S.M. Rashid², M. Sultan (Journal of Experimental Sciences, 2011)
Wetland ecosystems integrate many upstream processes and the differential contributions of spatially distributed controlling factors, especially land use / land cover. In view of the significant importance of wetlands in the ecosystem and regional economy, an attempt has been made to analyze the impact of land use / land cover dynamics on spatial status of Hokar Sar wetland, a Ramsar Site located in Kashmir Himalayas. The impact assessment has been carried out by analyzing the multi-temporal (1986, 1995, 2005) changes in the upstream land use / land cover characteristics of wetland watershed, by using remote sensing data of SPOT HRV-I, Landsat-ETM and IRS-LISS-III, respectively. The multi-temporal land use / land cover statistics revealed that significant changes have taken place from 1986 to 2005 in the watershed. And in response to these upstream watershed changes, the Hokar Sar wetland has exhibited changes in spatial extension, structure and hydrological characteristics. As a consequence of continuous inflow of sediment load and nutrients from the upper catchment due to changing land use, the wetland has fragmented into various spatial zones with varying physicochemical characteristics. Average water depth of the wetland has reduced significantly, wetland has attained eutrophication condition and the overall ecosystem of the wetland has been found to be degraded.